2021
DOI: 10.1007/978-1-0716-1358-0_14
|View full text |Cite|
|
Sign up to set email alerts
|

A User Guide for the Identification of New RiPP Biosynthetic Gene Clusters Using a RiPPER-Based Workflow

Abstract: In recent years, genome mining has become a powerful strategy for the discovery of new specialized metabolites from microorganisms. However, the discovery of new groups of ribosomally synthesized and post-translationally modified peptides (RiPPs) by employing the currently available genome mining tools has proven challenging due to their inherent biases towards previously known RiPP families. In this chapter we provide detailed guidelines on using RiPPER, a recently developed RiPP-oriented genome mining tool c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This class is characterized by the presence of labionin/avionin(s) (Figure 2) and an N-terminal lipid moiety. Microvionin (46), the first lipolanthine isolated from Microbacterium arborescens (Figure 19), has activity against MRSA and Streptococcus pneumoniae. 248 Goadvionin is another lipidated class III lanthipeptide and shows similar antibacterial activity.…”
Section: Lipolanthinesmentioning
confidence: 99%
See 1 more Smart Citation
“…This class is characterized by the presence of labionin/avionin(s) (Figure 2) and an N-terminal lipid moiety. Microvionin (46), the first lipolanthine isolated from Microbacterium arborescens (Figure 19), has activity against MRSA and Streptococcus pneumoniae. 248 Goadvionin is another lipidated class III lanthipeptide and shows similar antibacterial activity.…”
Section: Lipolanthinesmentioning
confidence: 99%
“…Based on the still limited information on RiPP MOA, the bioactivities associated with even closely related structural classes of RiPPs are rarely predictable. In some instances, elucidation of MOA and validation of biological targets for several compounds predate their characterization as members of a RiPP class. , As both the substrate peptide and the enzymes that catalyze the post-translational modifications are direct gene products, RiPP biosynthetic gene clusters are excellent candidates for genome mining exercises, and several available robust bioinformatics platforms harness this capability. Likewise, the synteny of genes necessary for the production of the bioactive RiPP final product has enabled refactoring efforts for heterologous production. In several instances, an affinity tag was appended to the precursor peptide, allowing for facile purification of the modified precursor peptide prior to removal of the leader sequence (Figure ) to yield high levels of purified compound as well as analogues .…”
Section: Introductionmentioning
confidence: 99%
“…Marriage of RODEO with gene finding algorithms like Prodigal can be useful, as shown with the program RiPPER, to locate the most probable short ORFs by evaluating ribosome binding sites (RBS), start codons, and G/C content. The candidate precursor peptides are then evaluated through machine learning algorithms (such as support vector machine classification), which identify traits of precursor peptides based on characterized RiPP pathways. , This task is often aided by sequence similarity networks (SSNs) and sequence alignments of the identified short ORFs, which point out the most probable precursor peptide(s) through sequence conservation. …”
Section: Introductionmentioning
confidence: 99%
“… 31 , 35 37 This task is often aided by sequence similarity networks (SSNs) and sequence alignments of the identified short ORFs, which point out the most probable precursor peptide(s) through sequence conservation. 40 44 …”
Section: Introductionmentioning
confidence: 99%
“…Most early investigations into RiPP natural products have been bioactivity-guided efforts leading to notable discoveries such as nisin, microcin B17, and darobactin. Advances in bioinformatic technologies, such as antiSMASH, BAGEL, RODEO, RiPPer, the tools of the Enzyme Function Initiative, and many others, have enabled rapid identification of RiPP BGCs within the ever-growing genome databases. , Consequently, renewed efforts have focused on the discovery of novel RiPPs by genome mining (e.g., refs and ). In addition, many studies have reported engineering of RiPP pathways to make new-to-nature structures and hybrid RiPPs. , A current bottleneck in such research is the identification of proteases that recognize the cognate RiPPs and remove the LP to yield the final, mature compound.…”
Section: Introductionmentioning
confidence: 99%